2011
DOI: 10.1007/s11191-011-9348-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Deterministic Views About Genes in Biology Textbooks: A Key Problem in Genetics Teaching

Abstract: A major source of difficulties in promoting students' understanding of genetics lies in the presentation of gene concepts and models in an inconsistent and largely ahistorical manner, merely amalgamated in hybrid views, as if they constituted linear developments, instead of being built for different purposes and employed in specific contexts. In this paper, we report the results of a study about how textbooks can provide the grounds for the students' construction of such hybrid views about genes. These views a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 77 publications
(90 reference statements)
1
28
0
5
Order By: Relevance
“…The finding that the models are largely hybrid has been raised also by Gericke & Hagberg (2010a) and Santos et al (2012), who suggest this incoherence is one of the main problems in genetics teaching. Another remarkable problem is the use of implicit multiple models in textbooks: as stated by Flodin (2009) upper secondary school students are probably unable to critically evaluate gene models as they weren't explicitly told there are different models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that the models are largely hybrid has been raised also by Gericke & Hagberg (2010a) and Santos et al (2012), who suggest this incoherence is one of the main problems in genetics teaching. Another remarkable problem is the use of implicit multiple models in textbooks: as stated by Flodin (2009) upper secondary school students are probably unable to critically evaluate gene models as they weren't explicitly told there are different models.…”
Section: Discussionmentioning
confidence: 99%
“…On a general level Justi & Gilbert (2000) suggested that the lack of understanding about different models creates an ahistorical understanding of science and makes it more difficult to understand the progress -and thus nature of science. There have been a number of studies arguing that problems in teaching the gene concept can cause learning problems (Santos et al, 2012;Flodin, 2009;Gericke & Hagberg, 2010a;Gericke & Hagberg, 2010b), but there has been a lack of studies on the issue. Gericke, Hagberg and Jorde (2013) actually tested students' understanding of multiple models: while the students recognized multiple models, they had difficulties in understanding them and identifying them in the text.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is even a growing international body of work exploring the links between persistent genetic determinism and persistently Mendelian ways of teaching, talking and thinking about genetics (see, e.g. Hagberg 2007, 2010a, b;Castéra et al 2008a, b;Dougherty 2010;Dougherty et al 2011;Santos et al 2012;Gericke et al 2013Thörne and Gericke 2014;Smith and Gericke 2015;Aivelo and Uitto 2015). Yet in practice Weldon's example has been indispensable.…”
Section: The Weldonian Perspectivementioning
confidence: 99%
“…Furthermore, different studies describe a diversity not only regarding learning and understanding, but also in educational materials for schools (Gericke and Hagberg 2010;dos Santos et al 2012) and in textbooks at college level (Albuquerque et al 2008;Flodin 2009). Studies of textbooks show that the gene concept (Flodin 2009) and genetic models (Gericke and Hagberg 2010) are often presented and explained in a variety of scientific contexts.…”
Section: Introductionmentioning
confidence: 99%